Dual-Source Energy Harvesting: Synergizing Solar and Rain-Induced Vibrations via Piezoelectric Systems Mounted Beneath PV Panels in Sarawak - Lawrence Sii, Ying Ting; Abadi, Chanik; Then, Yi Lung (2025)
The integration of renewable energy systems with complementary harvesting mechanisms offers a promising strategy to address the intermittency challenges of solar photovoltaic (PV) systems in tropical climates. This study investigates the feasibility of augmenting solar PV panels with piezoelectric harvesters mounted beneath them to capture low amplitude vibrations induced by rainfall, a seasonal phenomenon in Samarahan, Sarawak. Using MATLAB simulations and empirical vibration profiles derived from rain impacts, the proposed hybrid system is analyzed for its energy conversion efficiency under realistic climatic conditions. Key parameters, including piezoelectric material sensitivity, rectification losses, and storage capacitor dynamics, are evaluated to quantify the harvested energy. Simulation results reveal a maximum rectified voltage of 188.88 mV and an average harvested power of 0.01 μW from rain-induced vibrations, revealing the challenges of energy extraction from low-intensity environmental sources. While the vibrational contribution is modest compared to solar yields, the study demonstrates the potential for incremental energy gains in hybrid configurations, particularly during seasonal rainfall when solar irradiance is reduced. The work provides a methodological framework for modeling co-located energy systems in tropical regions and identifies critical barriers such as vibration amplitude limitations and diode losses to practical implementation. These findings lay the groundwork for optimizing piezoelectric materials and circuit designs to enhance energy recovery from ambient vibrations in regions with seasonal rainfall patterns like Sarawak.